Convalescent Plasma Therapy for COVID-19: Lessons from SARS-CoV, MERS-CoV, and H1N1 Infection - Parastoo Hosseini; Hakimeh Rahimi; Mahsa Mohammadi Najafabadi; Atousa Ghorbani; Shima Karbasi Najafabadi; Arezoo Faridzadeh; Javad Arabpour; Ehsan Khormali; Niloofar Deravi (Interna Publishing, 2021)
The global widespread mortality after the emergence of SARS-CoV-2 infection in China, has become a critical concern all around the world. Convalescent plasma (CP) therapy is one of the methods elevating the survival rate for COVID-19 infection cases. This technique, as a practicable therapy, was used in previous viral outbreaks including influenza, SARS and MERS. In CP therapy, the blood plasma is collected from persons rehabilitated from that specific infection in order to develop a passive immunity in other patients. Therefore, this review aimed to point out the role of CP therapy in aforementioned viral infections and illustrate different factors influencing the efficacy of CP therapy.